2018
DOI: 10.1097/md.0000000000013340
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative elevated neutrophil-to-lymphocyte ratio (NLR) and derived NLR are associated with poor prognosis in patients with breast cancer

Abstract: Background:Preoperative neutrophil-lymphocyte ratio (NLR) and derived NLR (dNLR) have been suggested to be correlated with the prognosis of patients with breast cancer (BC). However, the results still remain controversial. Therefore, this study was to further evaluate the prognostic potential of preoperative NLR and dNLR for BC patients using a meta-analysis.Methods:Relevant articles were sought in PubMed and Cochrane Library databases up to September 2018. The associations between preoperative NLR/dNLR and ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 46 publications
(51 reference statements)
6
53
0
Order By: Relevance
“…The results of our studies were in line with NSCLC treated with chemotherapy, nivolumab, and EGFR‐ tyrosine kinase inhibitors (TKIs) . Furthermore, the trend were same in breast cancer, colorectal cancer and liver cancer . Anti‐PD‐1 Nivolumab can induce cancer cell apoptosis via T‐cell activation and EGFR‐TKIs could inhibit the combination of tyrosine kinase and adenosine triphosphate (ATP).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The results of our studies were in line with NSCLC treated with chemotherapy, nivolumab, and EGFR‐ tyrosine kinase inhibitors (TKIs) . Furthermore, the trend were same in breast cancer, colorectal cancer and liver cancer . Anti‐PD‐1 Nivolumab can induce cancer cell apoptosis via T‐cell activation and EGFR‐TKIs could inhibit the combination of tyrosine kinase and adenosine triphosphate (ATP).…”
Section: Discussionsupporting
confidence: 71%
“…As platelets are part of the inflammation process, paraneoplastic thrombocytosis is common in solid cancer . There were some reports about the relationship between inflammation and prognosis, including neutrophils, lymphocytes, platelets and the combinations between them, such as neutrophils‐to‐lymphocytes rate (NLR), derived NLR (dNLR), platelets‐to‐lymphocytes rate (PLR) . In addition, hemoglobin (HGB) has been discovered to have an impact on prognosis, either .…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, in other molecular BC subtypes (luminal subtype: ER+ and/ or PR+ and HER2-; HER2-positive subtype: HER2+), no significant association between the NLR or the LMR and survival (DFS or OS) was identified [6]. Duan et al [7] also confirmed the role of the preoperative NLR as a predictive biomarker for prognosis in patients with BC. The NLR can also be a predictor of a pathologically completer response to neoadjuvant chemotherapy, especially with triple-negative BC [8].…”
Section: Discussionmentioning
confidence: 98%
“…Several studies and a recent meta-analysis have confirmed and extend the prognostic role of NLR in breast cancer [113][114][115]. However, Ferroni et al [115] demonstrated that the NLR may represent a negative prognostic factor to define distant metastasis-free survival, especially in stage I breast cancer, but not for local recurrence.…”
Section: Neutrophilsmentioning
confidence: 95%
“…Following their suggestions, the NLR prognostic value should be regarded with caution, and additional studies are required to consolidate the clinical value of NLR. Nevertheless, in stage I patients the presence of a high NLR might raise the question as to whether they should be more aggressively managed [113][114][115]. Furthermore, a retrospective study was performed to investigate the role of NLR in breast cancer patients receiving neoadjuvant chemotherapy [116]: the pCR rate in patients with low pre-treatment NLR (NLR < 2.06) was higher than in those with higher NLR (NLR ≥ 2.06) (24.5 vs.14.3%, p < 0.05).…”
Section: Neutrophilsmentioning
confidence: 99%